The Effect of Organizational Commitment and Occupational Stress on Psychological Stability Among a Sample of Nurses in Jeddah (The International Journal for Scientific Research, 2024)
The current study aims to find out the effect of organizational commitment and pressures on the psychological stability in a sample of (116) nurses in the city of Jeddah. Through a correlational approach, the results showed a statistically significant correlation between organizational commitment and psychological stability, as well as occupational stress and psychological stability. The results also showed that there were statistically significant differences in the level of psychological stability depending on the level of organizational commitment, as well as in professional stress, where the results showed that there were statistically significant differences between the averages of stability. The results also indicated the possibility of predicting psychological stability through organizational commitment and professional pressures, with a reduced role for organizational commitment in explaining psychological stability. In contrast to occupational pressures, which had the highest share in explaining psychological stability.
Keywords: Organizational Commitment; Occupational Stress; Psychological Stability; Nurses in the City of Jeddah